2021
DOI: 10.1021/acs.joc.1c00760
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoazapurines: Design, Synthesis, and Photophysical Study

Abstract: A highly efficient approach to a new class of polycyclic 8-azapurines, benzo­[4,5]­imidazo­[1,2-a]­[1,2,3]­triazolo­[4,5-e]­pyrimidines (BITPs), with good photophysical characteristics is proposed. The approach comprises condensation of aminobenzimidazoles with 3-oxo-2-phenylazopropionitrile to form 3-(arylazo)­benzo­[4,5]­imidazo­[1,2-a]­pyrimidine-4-amines, which undergo oxidative cyclization by the catalytic action of copper­(II) acetate, resulting in BITPs with 73–84% yield. Spectral investigations demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The monitoring of the reaction progress was performed by using TLC on Sorbfil plates (Imid LTD, Russia, Krasnodar) eluent is CHCl 3 . Heterocycles 3b, 3d, 3e, 7, 10a, 10b were synthesized in accordance with literature data: 3b [ 17 ] , 3d, 3e [ 18 ] , 7 [ 19 ] , 10a, 10b [ 20 ] . All synthesized compounds are >95% pure by elemental analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring of the reaction progress was performed by using TLC on Sorbfil plates (Imid LTD, Russia, Krasnodar) eluent is CHCl 3 . Heterocycles 3b, 3d, 3e, 7, 10a, 10b were synthesized in accordance with literature data: 3b [ 17 ] , 3d, 3e [ 18 ] , 7 [ 19 ] , 10a, 10b [ 20 ] . All synthesized compounds are >95% pure by elemental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…2021/056, 15 June 2021. All sections of this study adhere to the ARRIVE Guidelines for reporting animal research [ 20 ].…”
mentioning
confidence: 99%
“…The monitoring of the reaction progress was performed by using TLC on Silufol UV254 plates (eluent is CHCl3). Heterocycles 3b, 3d, 3e, 7, 10a, 10b were synthesized in accordance with literature data: 3b [16], 3d, 3e [17], 7 [18], 10a, 10b [19]. All synthesized compounds are >95% pure by elemental analysis.…”
Section: Chemistrymentioning
confidence: 99%
“…V. Fedotov and co-workers in 2021. 57 (Scheme 21) They screened various copper catalysts and it was observed that Cu(OAc) 2 ·H 2 O (1.0 equivalent) was the most effective catalyst. The yield of the desired product was improved (84%) by increasing the amount of the catalyst, Cu(OAc) 2 ·H 2 O (2.5 equivalent) at 100 °C.…”
Section: Transition Metal and Nhc Catalyzed Synthesismentioning
confidence: 99%
“…45,46 Several other methods have also been developed which are catalyzed by a variety of metals such as Palladium, [47][48][49] rhodium, 50,51 and Copper. [52][53][54][55][56][57] Greener alternatives have also been developed such as those being mediated by Iodine. [58][59][60][61] or synthesis being performed in the aqueous medium.…”
Section: Introductionmentioning
confidence: 99%